From telegrapher to Titan : the life of William C. Van Horne - Knowles, Valerie (Dundurn Group ; Dundurn Press, 2004)
"When the Canadian Pacific Railway's transcontinental line was completed six years ahead of schedule, CPR general manager William C. Van Horne insisted that any ceremonies to commemorate the event be kept informal, declaring: "There is to be no 'golden spike' driven on the completion of the Canadian Pacific and no excursion to celebrate the event. The last spike will probably be driven by one of our track-laying gang and will be an iron one."" "A man of action, William C. Van Horne was the prime mover of the CPR, an organization heading toward financial disaster when he took control in 1881. Described as "a human dynamo" for his energy and imagination, the tireless railway tycoon conducted thousands of workers toward the aim of uniting the Canadian east and west, chiselling access through what was heralded as impassable terrain, including the Canadian Shield, Rocky Mountains, and Fraser Valley." "Born in Illinois in 1843, by the time he was 38 years old, Van Horne already had 25 years' experience in the railway business, starting as a message delivery boy and telegrapher and rising to prominence in the United States before coming to steer Canada's national railway project. Later assuming the role of CPR president, Van Horne also became one of Canada's foremost financiers and art collectors, capping his career by opening Cuba's interior with a railway. After turning down the honour twice, Van Horne was knighted by Queen Victoria for his contributions toward Canadian unity."--Jacket